Ownership Structure, Capital Structure and the Audit Committees’ Effectiveness: - Abu Braik, Jamel Jamal; Al-Thuneibat, Ali Abedalqader (Journal of Accounting, Business and Management (JABM), 2023)
ABSTRACT The main purpose of this research is to investigate the impact of the capital structure and the ownership structure on the audit committee effectiveness. A sample of 35 service firms and 47 industrial firms that were continuously listed on Amman Stock Exchange during the years 2014 to 2018 with a 388 observation was used. Descriptive statistics and multiple regression analysis were used to analyze the data and test the hypotheses. The independent variables included ownership structure and capital structure, whereas the dependent variable represented by the audit committee effectiveness. A set of variables that formed the effectiveness index were taken into consideration, including the independence of the committee, the independence of its chairman, knowledge and expertise of its members, size of the audit committee and frequency of meetings. The study results revealed that there is a negative significant impact for the concentrated ownership and managerial ownership on the audit committee effectiveness, whereas, the institutional and the foreign ownership don’t show a significant impact. The results also revealed that there is a positive significant impact for the capital structure on the audit committee effectiveness. Based on the results of the study the researchers would recommend that more attention should be given by decision-makers to take the appropriate measures to improve the effectiveness of the audit committees in order to direct the attention of the various investing groups to the fact that these committees are in their interest and that they are already in their service.